2014
DOI: 10.1021/jo5006685
|View full text |Cite
|
Sign up to set email alerts
|

Possible Reason for the Unusual Regioselectivity in Nucleophilic Ring Opening of Trisubstituted Aziridines under Mildly Basic Conditions

Abstract: 2,2,3-Trisubstituted aziridines are known to undergo ring opening at the more substituted carbon under mildly basic conditions. However, the reason for the formation of the more sterically encumbered product has never been examined. Several trisubstituted aziridines, with different substitution patterns at the C-2 and C-3 carbons, were synthesized to change the electronics of the aziridine ring system. These changes had no effect on the regioselectivity of the ring-opening reaction. Using the B3LYP/6-31G* DFT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Next, rapid removal of the silyl protecting group furnished linear precursor 2 , which was suitably positioned for the key macrocyclization step. Gratifyingly, our methodology 22 in regio- and stereoselective ring opening of a trisubstituted aziridine translated well into the present intramolecular system despite concerns of creating a strained para -cyclophane ( Scheme 2 ). To the best of our knowledge, this is the first effective macrocyclization of a 14-membered cyclopeptide precursor with the chemically sensitive Z -enamide intact.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Next, rapid removal of the silyl protecting group furnished linear precursor 2 , which was suitably positioned for the key macrocyclization step. Gratifyingly, our methodology 22 in regio- and stereoselective ring opening of a trisubstituted aziridine translated well into the present intramolecular system despite concerns of creating a strained para -cyclophane ( Scheme 2 ). To the best of our knowledge, this is the first effective macrocyclization of a 14-membered cyclopeptide precursor with the chemically sensitive Z -enamide intact.…”
Section: Resultsmentioning
confidence: 84%
“…Starting from commercially available N -Boc- d -serine, known precursor 6 was prepared in five steps ( Scheme 2 ). 22b , 25 Pinnick oxidation 22 , 23d to the corresponding acid 5 , followed by EDCI-mediated coupling with free amine of l -leucineamide afforded the amino alcohol 7 in good yield. Mitsunobu cyclization 22 , 23a , b , d furnished the desired trisubstituted aziridine ( 3 ), and its structure was secured by X-ray crystallographic analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…45−47 The calculation study indicated that the presence of an alkynyl group stabilizes the transition state and lowers the activation energy needed for this pathway. 48 We speculated that the beneficial effect of an alkynyl group in aziridine ring opening could also be implanted by the 2-oxazolidinone-moiety of 4, as the ring strain is relieved when the ring opening occurs at the tertiary carbon. Indeed, ring-opening reactions of mono-and disubstituted, 2-oxazolidinone-fused aziridines have been studied 49,50 and nicely applied.…”
mentioning
confidence: 99%